2020
DOI: 10.1007/s11240-020-01835-0
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of maize-produced porcine epidemic diarrhea virus spike protein elicits neutralizing antibodies in pigs

Abstract: Porcine Epidemic Diarrhea Virus (PEDV) causes severe diarrhea and mortality in piglets. Robust immunity may break the transmission cycle. Expression of antigens in maize grains is a promising method for producing low-cost vaccines. As a first step, we expressed maize constructs containing PEDV S1 spike protein targeted to various cellular locations including the cell wall, endoplasmic reticulum, and vacuole, and fused to carrier proteins E. coli heat labile subunit (LTB) and a dendritic cell (DC) binding pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Another study showed that systemic anti-R1 antibody levels were significantly higher in mice orally vaccinated with recombinant R1-LTB protein compared to those vaccinated with R1 alone. In line with these reports, LTB fusion with the C-terminal fragments of botulinum neurotoxins (BoNTs) serotypes C and D [20] , hyopneumoniae antigens [21] , A. pleuropneumoniae toxin epitopes [22] , dengue envelope protein domain III-LTB [4] , porcine epidemic diarrhoea virus spike protein [23] and influenza A virus epitopes (IAVe) [24] , induced broad humoral and cellular immune responses and improved protection against viral challenge in various animal models.…”
Section: Introductionmentioning
confidence: 58%
“…Another study showed that systemic anti-R1 antibody levels were significantly higher in mice orally vaccinated with recombinant R1-LTB protein compared to those vaccinated with R1 alone. In line with these reports, LTB fusion with the C-terminal fragments of botulinum neurotoxins (BoNTs) serotypes C and D [20] , hyopneumoniae antigens [21] , A. pleuropneumoniae toxin epitopes [22] , dengue envelope protein domain III-LTB [4] , porcine epidemic diarrhoea virus spike protein [23] and influenza A virus epitopes (IAVe) [24] , induced broad humoral and cellular immune responses and improved protection against viral challenge in various animal models.…”
Section: Introductionmentioning
confidence: 58%
“…The extensive coverage of the detected peptides of the inserted protein sequence and their presence in all three Enz transgenic developing protein samples with the absence of these peptides in the nontransgenic sample, indicates that the inserted aflatoxin-degrading enzyme is stably produced in developing maize kernels and it has accumulated to appreciable levels to be detected by mass spectroscopy. The subcellular targeting strategy used to express the aflatoxin-degrading enzyme likely enhanced the amount of this enzyme that accumulated in maize developing kernels, as this stabilization strategy has been shown to considerably elevate amounts of inserted proteins in maize kernels (for example [ 47 , 48 ]) and other crop seeds [ 37 , 39 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work demonstrated that the S1 antigen could accumulate to high levels in maize and allow for a heat-stable, low-cost production supply of the antigen [33]. In addition, 27-day-old pigs fed maize-produced S1 protein developed high levels of sera neutralization antibodies after being challenged with active PED virus [33]. However, because the disease symptoms are acute only in nursing pigs, protection from the virus could not be evaluated in this study.…”
Section: Introductionmentioning
confidence: 92%
“…Nonetheless, there is only one report expressing the core neutralizing epitope (COE) domain of the PEDV spike protein in maize, which was subsequently purified and injected in mice to elicit antibodies against PEDV [32]. Our previous work demonstrated that the S1 antigen could accumulate to high levels in maize and allow for a heat-stable, low-cost production supply of the antigen [33]. In addition, 27-day-old pigs fed maize-produced S1 protein developed high levels of sera neutralization antibodies after being challenged with active PED virus [33].…”
Section: Introductionmentioning
confidence: 99%